Morphological variability of native maize (Zea mays L.) of the west highland of Puebla and east highland of Tlaxcala, Mexico - Alvarado-Beltrán, Gregorio; López-Sánchez, Higinio; Santacruz-Varela, Amalio; Muñoz-Orozco, Abel; Valadez-Moctezuma, Ernestina; Gutiérrez-Espinosa, Ma. Alejandra; López, Pedro A.; Gil-Muñoz, Abel; Guerrero-Rodríguez, Juan de Dios; Taboada-Gaytán, Oswaldo R. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
The objective of this research was to assess the morphological variability of maize landraces native of the west highland of Puebla and east highland of Tlaxcala, México, in order to, besides define it, related it to races, commercial varieties and with the altitude of the localities of seed collection. The genetic resources evaluated were 134 accessions collected in 34 localities, along with 10 controls. Experiments were established on three localities using a Lattice 12 x 12. Thirty-two morphological traits were analyzed, 27 of them resulting with highly significant differences, reflecting the high variability at the level of morphological characters, many of them of agronomic interest. From variance analysis 16 traits were selected for use in a cluster analysis through the Modified Localization Method, which joint the populations in six groups, most of them in the group 1, with morphological traits of long cycle varieties: high plants, with greater primary branches of the tassel, greater ear diameter and length, and greater grain length and width. The conclusions indicate that the morphological variability of Landraces is not associated with the altitude of localities of seed collection and that these have more relation with Chalqueño race, small with Conico race, absent with Conico Norteño and Palomero Toluqueño races and almost absent with commercial varieties.